Reinforced, Extruded, Isotropic Magnetic Elastomer Composites: Fabrication and Properties - Marcin Masłowski; Justyna Miedzianowska; Krzysztof Strzelec (Advances in Polymer Technology)
The study involves the development of isotropic magnetorheological elastomer composites (i-MREs) with improved mechanical properties, their preparations, and properties characterizations. The novelty of the research is the use of extrusion process in the preparation of composites containing two different fillers: carbonyl iron powder (CIP) as magnetic filler and carbon black (FEF, N550) as reinforcing one. So far, the process of extrusion has been used to prepare magnetic composites without filler that improve mechanical properties. It is worth mentioning that the polymer matrix (ethylene-octene copolymer, EOR) offers excellent performance in extrusion applications. In this research, two methods of magnetic composites preparation were reported: traditional, during two-roll mill, and a new one using extrusion process. It was found that the usage of new processing technology allowed forming more homogenous dispersion of particles in elastomer matrix and oriented polymer chains, resulting in an improved rheometric characteristic, increased crosslink density, and decrease of the storage modulus (Payne effect). Based on both static/dynamic mechanical properties and damping properties under the influence of compression stress, the positive influence of extrusion process on material characteristics was confirmed. Moreover, all composites proved very good magnetic properties and resistance to thermooxidative ageing.